KONDISI EKSISTING DESTINASI PARIWISATA PANTAI LASIANA KOTA KUPANG BERDASARKAN ATRAKSI, AKSESIBILITAS, FASILITAS, KELEMBAGAAN, DAN EKOSISTEM PARIWISATA - Habaora, Fellyanus; Riwukore, Jefirstson Richset; Yustini, Tien (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
The purpose of the study was to determine and analyze the existing condition of the Lasiana Beach tourism destination in Kupang City based on attractions, accessibility, facilities, institutions, and tourism ecosystems. The research took at Lasiana Beach, Kupang City, from July – December 2019 using Research and Action Research designs and descriptive approach techniques. Determination of samples by cross-section or available samples. The data were analyzed by sorting information and descriptions of the points from the observations, interviews, and documentation carried out. The results showed that the highest tourist attraction for Lasiana Beach was for swimming and the lowest for nature schools. Most tourists complain about the accessibility to tourist destinations. However, most tourists feel that the facilities at the tourist sites are quite complete. The role of tourism institutions is considered lacking while people visit a destination because they often visit it and are invited. The tourism ecosystem still looks weak in terms of investment, policies, and tourism resources. Recommendations are diversification of attractions, improvement of the physical condition of facilities and the involution of tourist facilities, the effectiveness of marketing and promotion of tourist destinations, increasing the role of the public, and improving the accessibility of tourist destinations.